Inhibitory effects of Syzygium jambos extract on biomarkers of endothelial cell activation - Yaritza Inostroza-Nieves; Shirley Valentin-Berrios; Christopher Vega; Gregory N. Prado; Claribel Luciano-Montalvo; José R. Romero; Alicia Rivera (BMC, 2022)
Abstract Background Disordered endothelial cell activation plays an important role in the pathophysiology of atherosclerosis, cancer, sepsis, viral infections, and inflammatory responses. There is interest in developing novel therapeutics to regulate endothelial cell function in atherothrombotic, metabolic, vascular, and hematological diseases. Extracts from leaves of the Syzygium jambos (L.) Alston (S. jambos) trees have been proposed to treat cardiovascular diseases and diabetes through unclear mechanisms. We investigated the effects of the S. jambos extract on biomarkers of endothelial dysfunction and immune responses in the human endothelial cell line, EA.hy926. Methods Leaves of S. jambos were collected, concocted and lyophilized. To study the effects of S. jambos on endothelial cell activation, we used the human endothelial cell line. IL-6 levels were measured using qPCR and ELISA. PDI activity was measured using Insulin Turbidity and Di-E-GSSG assays. CM-H2DCFDA was used to study ROS levels. Migration assay was used to study S. jambos effect on ex vivo human polymorphonuclear and human mononuclear cells. Results Our results show that incubation of EA.hy926 cells with ET-1 led to a 6.5 ± 1.6 fold increase in IL-6 expression by qPCR, an event that was blocked by S. jambos. Also, we observed that ET-1 increased extracellular protein disulfide isomerase (PDI) activity that was likewise dose-dependently blocked by S. jambos (IC50 = 14 μg/mL). Consistent with these observations, ET-1 stimulated ex vivo human polymorphonuclear and mononuclear cell migration that also was dose-dependently blocked by S. jambos. In addition, ET-1 stimulation led to significant increases in ROS production that were sensitive to S. jambos. Conclusion Our results suggest that the S. jambos extract represents a novel cardiovascular protective pharmacological approach to regulate endothelial cell activation, IL-6 expression, and immune-cell responses.